1969
DOI: 10.1149/1.2411852
|View full text |Cite
|
Sign up to set email alerts
|

Etching Characteristics of Silicon Carbide in Hydrogen

Abstract: It was found that the etching rate of alpha (hexagonal) silicon carbide in hydrogen at high temperatures (above 1550~varies with the susceptor material on which the inductively heated silicon carbide rests. Molybdenum exhibits the most pronounced effect increasing the etching rate by about one order of magnitude over that on all other susceptors (W, Nb, Ta, C) employed. Finite etching rates were also observed on a-silicon carbide exposed to inert gas atmospheres at elevated temperatures and were attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1971
1971
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
7
0
Order By: Relevance
“…ID, horizontal, water-cooled, quartz reaction tube using a silane-propane mixture and hydrogen as carrier gas. Details of the experimental arrangement and procedure have been described elsewhere (3). The substrates, (0001) platelets of ~-SiC, were polished with 3~ diamond paste, chemically etched in an alkaline ferricyanide solution (4), and thermally etched in hydrogen at 1650~…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ID, horizontal, water-cooled, quartz reaction tube using a silane-propane mixture and hydrogen as carrier gas. Details of the experimental arrangement and procedure have been described elsewhere (3). The substrates, (0001) platelets of ~-SiC, were polished with 3~ diamond paste, chemically etched in an alkaline ferricyanide solution (4), and thermally etched in hydrogen at 1650~…”
Section: Methodsmentioning
confidence: 99%
“…The computation of the equilibrium concentrations of the thermodynamically stable species (gaseous and solid) in the present system was carried out with a program (2) based on minimizing the total Gibbs free energy with the constraint of conservation of mass (3). The accuracy of the program was tested by applying it to similar systems for which experimental results were available (4).…”
Section: Introductionmentioning
confidence: 99%
“…In H 2 annealing, the SiC surface is exposed to hydrogen flow at temperatures of 1400-1700°C. [3][4][5][6][7][8][9][10] Moreover, dangling bonds on SiC surfaces are terminated after etching with atomic hydrogen above 1100°C. 11 Saidov et al have shown that the character of SiC etching depends not only on the temperature and velocity of the gas flow, but on the heater as well.…”
mentioning
confidence: 99%
“…They surmised that the etch rate was limited by the concentration of hydrogen atoms. Previous investigations by Harris et al 14 found the etch rate of SiC to be dependent upon the susceptor material which supports the formation of atomic hydrogen due to the different catalytic properties of the different materials. Also, Nakamura et al 15 showed that stepped surfaces may be obtained on SiC͑0001͒ at temperatures around 1300°C when using HCl/H 2 mixtures, indicating the necessity of atomic hydrogen for this process.…”
Section: A Thermodynamic Considerationsmentioning
confidence: 76%